Description of the feeding preferences of triatominae in the Chagas disease surveillance study for the State of Pernambuco, Brazil (Hemiptera: Reduviidae) - Maria Beatriz Araújo Silva; Kelly Reis de Menezes; Maria Clara Guerra de Farias; Maria Sandra Andrade; Caio Cesar Alves Victor; Elias Seixas Lorosa; José Jurberg (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Studying the feeding preferences of triatomines is an important entomological surveillance tool, since continuous surveillance of the disease is necessary. METHODS: The precipitin reaction was used to describe the feeding preferences of triatomines along with their natural infection by flagellates similar to Tyrpanosoma cruzi. Six hundred eighty-seven insects were examined, including Triatoma brasiliensis, Triatoma pseudomaculata, and Panstrongylus lutzi. RESULTS: Sixty-nine (10%) of 687 triatomines examined tested positive for flagellates similar to T. cruzi, and 8 (1.2%) of these fed on human blood. CONCLUSIONS: This study found potential transmitters of Chagas disease both inside and outside the domiciliar environment.